Flexible studies at AeU - The, Star (the star, 2014)
AeU's collaboration with State Polytechnic of Jakarta, Indonesia has produced graduates of Bachelor of Information and Communications Technology (HONS). Nana Puspita Sari " I really enjoyed the communication class which were conducted outdoors and away from the classroom setting."